HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PERILAKU PEMBERIAN ASI EKSKLUSIF PADA PADA IBU YANG MEMPUNYAI BAYI USIA 6-12 BULAN DI RUMAH SAKIT MURNI ASIH TAHUN 2021 - Mira Suminar; Siti Ulfah (STIKes IMC Bintaro, 2022)
Exclusive breastfeeding is breastfeeding from the time the baby is born until the baby is 6 months old. Exclusive breastfeeding coverage for infants 0-6 months in Indonesia in 2015 was 55.7%. This figure is still far from the target to be achieved, which is 80%. So it is necessary to study the factors that cause the low coverage of exclusive breastfeeding. Mother is considered as the most important factor in exclusive breastfeeding. For this reason, it is necessary to do research on the relationship between knowledge and attitudes of mothers with exclusive breastfeeding. This type of research is an analytic survey with a cross sectional design. Analysis of the data using the chi square test with a sample of 32 mothers who have babies aged 6-12 months. This study aims to see the relationship between knowledge and attitudes of mothers with exclusive breastfeeding carried out at Murni Asih Hospital, Tangerang Regency. The results showed that there was no relationship between respondents' knowledge and exclusive breastfeeding (ρ = 0.672), and there was a relationship between respondents' attitudes and breastfeeding. Exclusive breastfeeding (p = 0.044). From the results of the study, it was found that most of the mothers did not give breast milk for reasons of work and too little breast milk approached the age of 6 months. So the suggestion from the researcher is that health workers can provide health education to mothers in an effort to increase breast milk and how to prepare breast milk so that it can still be given to babies while the mother is working.